Leucine 41 is a gate for water entry in the reduction of Clostridium pasteurianum rubredoxin - Min, Tongpil (Cold Spring Harbor Laboratory Press, 2001)
Biological electron transfer is an efficient process even though the distances between the redox moieties are often quite large. It is therefore of great interest to gain an understanding of the physical basis of the rates and driving forces of these reactions. The structural relaxation of the protein that occurs upon change in redox state gives rise to the reorganizational energy, which is important in the rates and the driving forces of the proteins involved. To determine the structural relaxation in a redox protein, we have developed methods to hold a redox protein in its final oxidation state during crystallization while maintaining the same pH and salt conditions of the crystallization of the protein in its initial oxidation state. Based on 1.5 Å resolution crystal structures and molecular dynamics simulations of oxidized and reduced rubredoxins (Rd) from Clostridium pasteurianum (Cp), the structural rearrangements upon reduction suggest specific mechanisms by which electron transfer reactions of rubredoxin should be facilitated. First, expansion of the [Fe—S] cluster and concomitant contraction of the NH • • • S hydrogen bonds lead to greater electrostatic stabilization of the extra negative charge. Second, a gating mechanism caused by the conformational change of Leucine 41, a nonpolar side chain, allows transient penetration of water molecules, which greatly increases the polarity of the redox site environment and also provides a source of protons. Our method of producing crystals of Cp Rd from a reducing solution leads to a distribution of water molecules not observed in the crystal structure of the reduced Rd from Pyrococcus furiosus. How general this correlation is among redox proteins must be determined in future work. The combination of our high-resolution crystal structures and molecular dynamics simulations provides a molecular picture of the structural rearrangement that occurs upon reduction in Cp rubredoxin.